Analysis of the Influence of Financial Performance on BPRS Market Share 2019-2024 - Caecilia Oktavia Septiana Putri; M.Thoha Ainun Najib (Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: Indonesia’s economic development is closely related to the performance of the banking sector, particularly BPRS. Market share is an important indicator of BPRS success and is influenced by internal financial performance factors such as ROA, CAR, BOPO, NPF, and FDR. However, empirical data show fluctuating trends and previous studies report mixed results, highlighting the need for further research on the relationship between financial performance and market share. Research Methods: This study employs a quantitative associative approach using quarterly secondary data from BPRS financial reports for the period 2019–2024 to examine the effect of ROA, CAR, BOPO, NPF, and FDR on market share. Results: The results show that ROA, BOPO, and FDR have a significant partial effect on market share, while CAR and NPF do not. Simultaneously, all variables significantly influence the BPRS market share. Conclusion: The study concludes that BPRS market share is strongly influenced by internal financial performance, particularly ROA, BOPO, and FDR, indicating that improving efficiency and intermediation performance is essential to enhance market share.